(3eSCdI aj QLd bGd Ef Gddg de jcde ehSi JcdjeGs
(3ChdgG (B:s
(3eSFdI aj QLd bGd Cf Gddg de jcde ehSi JcdjeG hEfeG Ndb GdcdGe hGdUhJ ajGdTLQI hehSi Ydjg SeY ef GdTLQg dG ef Gddg s
(3BNQgG (B:s
(3hCHhGdMSf Hf ehSi GdCTYQi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B28s
(3GdfSNI HgG MhGTs
(3hQOJ CjVkG JMJ Qbe (B27/430s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJhMjO hGdedd hGdfMds